Respon Pemerintah dan Pengusaha Lokal dalam Menangani Masalah “Zero-Dollar Tourist” Cina di Bali - Putra, Adhitia Pahlawan; Bahri S, Andi (Jurnal Kajian Bali (Journal of Bali Studies); Vol 11 No 2 (2021): Volume 11 No. 2. Oktober 2021DO - 10.24843/JKB.2021.v11.i02.p04, 2021)
In 2017, Bali visited by 1.3 million Chinese tourist. This great number positively appreciated for the local socio-economic benefit. However, unfortunately it led to serious concern because of the ‘zero-dollar tourist’ issue, the tourist that contributed nothing on the island as all payment cash, fee, and commissions went back to China. This article identifies the raise of Chinese tourist in Bali, the response of tourism stakeholders, and Governmental policy innovations to win the zero-dollar tourist. The data sourced from newspaper, research reports, interviews, and online article journals as well as online video. The results indicated that the visit of Chinese tourists in Bali, specifically before the pandemic Covid-19, was affected by the inter-government cooperation policies, aviation supplies, and tourism advertising. The high quantity visitors of Chinese tourist were responded positively, but the practice of zero-dollar tourist was caused the negatively point of view. The Bali Government shut the illegal Chinese-related souvenir shops down and encouraged travel agent to take Chinese tourist to shopped in locally-owned outlets.